Eco-friendly bio-medical waste management technology practice in Bangladesh for sustainable development / Mohammed Ali Arshad Chowdhury and Md. Zahedul Islam - Chowdhury, Mohammed Ali Arshad; Islam, Md. Zahedul (Universiti Teknologi MARA, Perak, 2023)
Currently Sustainable Development Goals (17 goals) are the main challenges for industrialization and infrastructure development for an economy. One challenge faced is in developing economy like Bangladesh where the focus of industrialization has been given priority by sacrificing natural conservation. Recently a large number of health cares have been established all over the country. Therefore, a huge amount of medical wastage is generated daily and Bio-medical waste management is inevitable for sustainable development. The management of bio medical waste is directly relevant to SDG goal 3 (Good health and well-being), 6 (Clean water and sanitation), 11(Sustainable cities and communities), 13(Climate action) and 15(Life on land). From the literature, it has been found that few eco-friendly waste management technologies are available and adopted by various countries. This paper aims to identify the bio-medical waste management practice in Bangladesh and whether it is eco-friendly or not. A survey was conduced to 176 respondents from 22 healthcare institutions; the study showed that most of the health care institutions transfer their medical wastage to the responsible municipality/local authority. In addition, opinions of the responsible environmental managers concern health care institutions confirmed the lack in capacity of executing eco-friendly bio2 Malaysian Journal of Sustainable Environment medical waste management technologies in Bangladesh. By using the result of this study, it is hoped healthcare institutions of developing countries like Bangladesh can apply eco-friendly waste management technology for ensuring sustainable development.